2011
DOI: 10.1111/j.1365-2265.2011.04009.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum TSH related to measures of body mass: longitudinal data from the HUNT Study, Norway

Abstract: Weight gain is accompanied by increasing TSH, and weight loss in women is related to decreasing TSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
86
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 32 publications
12
86
3
1
Order By: Relevance
“…However, the Norwegian population has long been considered to be iodine sufficient (15), and it seems unlikely that changes in iodine intake may explain the changes that we observed. Smoking (16,17), alcohol consumption (18), and adiposity (19,20,21) are other factors that could influence the prevalence of hypothyroidism or prevalence of high TSH concentrations, but statistical adjustment for differences in smoking habits, alcohol consumption, and BMI between the surveys did not substantially influence the changes in prevalence in our study.…”
Section: Huntmentioning
confidence: 56%
“…However, the Norwegian population has long been considered to be iodine sufficient (15), and it seems unlikely that changes in iodine intake may explain the changes that we observed. Smoking (16,17), alcohol consumption (18), and adiposity (19,20,21) are other factors that could influence the prevalence of hypothyroidism or prevalence of high TSH concentrations, but statistical adjustment for differences in smoking habits, alcohol consumption, and BMI between the surveys did not substantially influence the changes in prevalence in our study.…”
Section: Huntmentioning
confidence: 56%
“…Most population-based studies in healthy (non-LT4 treated) subjects have shown a direct correlation between serum TSH levels within the reference range and body weight, BMI, or fat mass (reviewed by Garin et al) (40), suggesting a role for thyroid-inducible metabolism on body weight and composition. Longitudinal studies have been more divergent, with some but not all studies reporting a correlation between baseline TSH, fT4, or fT3 and weight gain over time (40)(41)(42)(43)(44)(45). However, the correlations have been in different directions, and the point has been raised that weight change may affect thyroid hormone levels, rather than thyroid hormones affecting weight change (46).…”
Section: Lt4 Therapy Energy Expenditure and Body Compositionmentioning
confidence: 99%
“…In previous studies, we and others have found an association between serum TSH within the reference range and serum lipid levels (5,6), body weight (7,8), and blood pressure (9). Altered serum TSH level appears to be an important risk factor for disease in general.…”
Section: Introductionmentioning
confidence: 99%